ANALISIS PENDIDIKAN MORAL AGAMA DALAM KELUARGA DI KABUPATEN SIDOARJO - khusnulkh ninanur (PRODI PGSD STKIP PGRI SIDOARJO, 2022)
The purpose of this study was to find out how important religious moral education is in the family. Because humans are resources that need to be educated as the next generation of the nation. In the family environment, parents hold responsibility for children as a mandate and gift from Allah SWT. The development of religious moral values ​​means that children will have the character of a child, good manners, willingness to carry out religious teachings in everyday life. according to (Nuzul, 2011) moral education will continue to develop with various opinions and aspects of character, moral and religious values. Through this religious education, it is hoped that individuals can develop the potential of piety to Allah SWT. If this potential is well developed, the individual will be able to control himself in order to avoid forms of behavior that are contrary to the religious values ​​embedded in him. And one of them is family. Family education is the initial phase and the basis for one's education. It is also the center of natural education which takes place in a natural manner. Based on the results of observations made in January 2023 in one of the families in Sidoarjo Regency. The role of education in the family environment began to erode with society's life which began to be materialistic, where parents began not to play a big role as educators where children first get education, both morality. Because it can have a positive impact on children, moral education should be taught to children as early as possible.